PENGARUH KONSENTRASI DAN FREKWENSI PEMBERIAN PUPUK DAUN TERHADAP PERTUMBUHAN PANILI DI PEMBIBITAN - Rosihan Rosman; S Soemono; Suhendra Suhendra (Pusat Penelitian dan Pengembangan Perkebunan, 2004)
Research on the effect of concentration and frequency of foliar fertilizer application on growth of vanilla (Vanilla planifolia Andrews) was carried out at the experimental garden of The Indonesian spice and medicinal crops Research Institute, West Java, from May until October, 1996. The experiment was conducted with a randomized block design, with 3 replicates and 10 treatments. The treatments were control, 1,5 g foliar fertilizer/4 liter/twice a week, 1,5 g foliar fertilizer/4 liter/once a week, 1,5 g foliar fertilizer/4 liter/once in two weeks, 3 g foliar fertilizer/4 liter/twice a week 3 g foliar fertilizer/4 liter/once a week, 3 g foliar fertilizer/4 liter/ once in two weeks 4,5 g foliar fertilizer/4 liter/twice a week 4,5 g foliar fertilizer/4 liter/once a week, and 4,5 g foliar fertilizer/4 liter/once in two weeks. The foliar fertilizer used was NPK (30-10-10) plus trace elements, such as Fe, Co, B, Mo, Mg and vitamine B1. The result showed that application of 1,5 g foliar fertilizer/4 liter/twice a week and 4,5 g foliar fertilizer/4 liter/once in two weeks were the best for the growth of vanilla at nursery. However, application of 4,5 g foliar fertilizer/4 liter/once in two weeks is efisien.